A Modern Perspective on the History of Moldovan Statehood a Century Ago - Stepanov, Vyacheslav P. (Žurnal frontirnyh issledovanij, 2024)
The review highlights the monographic study by Galushchenko, O. S. (2024). One hundred years of the Moldavian ASSR. Moldavian statehood east of the Dniester. LAMBERT Academic Publishing (ISBN: 978‑620-7-63910-6). The researcher makes an attempt to analyze the development of historical events by bringing new facts discovered in recent times to their coverage and analysis. The book is characterized by attention to the subjective factor, which, in the author’s fair opinion, played not the least role in the creation of Moldovan autonomy and its further destiny. As it seems, O. S. Galuschenko’s book touches another important problem, which goes beyond the limits of the Left-Bank Subnistria, namely, the formation and dynamics of Moldovan statehood. In the context of this problem, the events covered in the monograph are only a segment, but a fundamental one, in the development of Moldovan state identity, which received a special resonance in the last years of existence and after the collapse of the USSR, when the Moldovan community split into supporters of the preservation of Moldovan statehood and adherents of unification with neighbouring Romania. Understanding that the researcher did not set a special goal of highlighting the dynamics of Moldovan state identity, the reviewer, alongside with analyzing the merits of Oleg Galuschenko’s monographic study, attempts to shortly overview the issue of Moldovan identity, resonating differently in the minds of the inhabitants of the left and right coasts of Moldova with particular force and urgency, especially with the coming to power of the current president M. Sandu and the majority of her party dominating in the parliament of the country, who are oriented to the levelling of Moldovan values, joining the European Union (which will lead to the dissolution of Moldova in Romania), integrating with NATO, dragging the country into the armed confrontation of the collective West with Russia in Ukraine.